2007
DOI: 10.1074/jbc.m607234200
|View full text |Cite
|
Sign up to set email alerts
|

Cdk5 Regulates STAT3 Activation and Cell Proliferation in Medullary Thyroid Carcinoma Cells

Abstract: The biological behaviors of thyroid cancer are varied, and the pathological mechanisms remain unclear. Some reports indicated an apparent aggregation of amyloid accompanying medullary thyroid carcinoma (MTC). Amyloid aggregation in neurodegeneration leads to hyperactivation of Cdk5 and subsequent neuronal death. Based on the connection with amyloid, the role of Cdk5 in MTC is worthy of investigation. Initially, the expression of Cdk5 and its activator, p35, in MTC cell lines was identified. Cdk5 inhibition by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
95
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(102 citation statements)
references
References 42 publications
(59 reference statements)
7
95
0
Order By: Relevance
“…33 CDK5 was also previously shown to enhance tumor cell proliferation and invasion. [28][29][30]34 CDK5's targets include several important proteins for cell growth and death, such as STAT3, AKT, BCL-2, p53, and RB. 29,[34][35][36][37] By testing multiple CDK5 siRNAs and shRNAs, we confirmed that CDK5 knockdown sensitizes genetically variable myeloma cell lines to bortezomib and other proteasome inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…33 CDK5 was also previously shown to enhance tumor cell proliferation and invasion. [28][29][30]34 CDK5's targets include several important proteins for cell growth and death, such as STAT3, AKT, BCL-2, p53, and RB. 29,[34][35][36][37] By testing multiple CDK5 siRNAs and shRNAs, we confirmed that CDK5 knockdown sensitizes genetically variable myeloma cell lines to bortezomib and other proteasome inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30]34 CDK5's targets include several important proteins for cell growth and death, such as STAT3, AKT, BCL-2, p53, and RB. 29,[34][35][36][37] By testing multiple CDK5 siRNAs and shRNAs, we confirmed that CDK5 knockdown sensitizes genetically variable myeloma cell lines to bortezomib and other proteasome inhibitors. This finding and its clinical relevance were further explored by the use of CDK5 inhibitors, roscovitine and SCH727965, which were demonstrated to synergize with bortezomib to induce cytotoxicity of both MM cell lines and primary MM samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with other CDKs, CDK5 is considered to be an essential regulator of neuronal differentiation, rather than a cell cycle regulator; and controls a wide range of functions, including synapse formation, neuronal migration and axon guidance (7), all of which indicate that CDK5 is important as a 'migration mediator'. Notably, CDK5 had been found to be correlated with increased invasion in prostate carcinoma, glioblastoma multiforme (8,9), pancreatic cancer cells (10,11) and medullary thyroid cancer (12). The inhibition of the activity of CDK5 decreases cancer cell migration and invasion (13), however, the mechanism underlying the involvement of CDK5 in tumorigenesis remains to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…There is presently a substantial amount of data to indicate that CDK5 plays important roles in extraneuronal cells during the process of myogenesis, lens differentiation, spermatogenesis, insulin secretion, apoptosis of ovarian cells and hematopoietic cell differentiation. 3,[5][6][7][8][9][10][11] Furthermore, CDK5 has been suggested to play roles in the regulation of motility of prostate cancer cells, 12 control of glioblastoma cell invasion, 13 modulation of proliferation of medullary thyroid carcinoma cells 14 and apoptotic control of leukemia cells. 15 These potential roles of CDK5 activity in the carcinogenesis of each cell type seem to involve distinct target substrates.…”
Section: Introductionmentioning
confidence: 99%